Differences in the content of five bioactive components in Dendropanax dentiger (Harms) Merr. from different production areas and their correlation with geographic distribution and climatic factors - Lan, Lan; Mao, Jiale; Chen, Weiqun; Liu, Shuang; Li, Tao; Zhou, Xiaohui; Chen, Tongtong; Yuan, Zhouxin; Lei, Houxing; Hu, Zhen; Zhang, Zhengchun; Wu, Shaochang; et al. (Frontiers in Pharmacology, 2026)
ObjectivePrevious research on Dendropanax dentiger (Harms) Merr. has primarily focused on isolating and identifying its chemical constituents and evaluating pharmacological activities such as anti-inflammatory effects. This study aimed to characterize the geographical variation in the contents of five major bioactive components in roots across different regions and to examine their associations with geo-climatic factors.MethodsChromatographic fingerprint analysis was performed on 23 batches of D. dentiger samples. Following chemometric analysis of the fingerprint data, five differential components, eleutheroside B, chlorogenic acid, saikolignanoside A, isochlorogenic acid A, and isochlorogenic acid C, were identified and subsequently quantified. The differences in the content of these components among samples from the five provinces were compared using one-way ANOVA. Furthermore, correlation and path analyses were performed to examine the relationships between the component contents and eight geographical-climatic variables.ResultsThe five bioactive components exhibited significant regional variation. Correlation analysis revealed the following relationships: The accumulation of eleutheroside B was correlated with precipitation in February, April, and December. Chlorogenic acid content showed correlations with precipitation in September, as well as with longitude and altitude within the studied range. Saikolignanoside A was correlated with precipitation in April, September, and December, solar radiation in April, and longitude. The content of isochlorogenic acid A correlated with precipitation in September, October, and December. Lastly, the accumulation of isochlorogenic acid C was associated with precipitation in February, April, September, October, and December.ConclusionThe content of five bioactive constituents in D. dentiger exhibited geographic variation across production areas, which was closely associated with precipitation in specific months, solar radiation, and geographical coordinates (longitude and altitude). These findings provide a reference for exploring the ecological causes of the D. dentiger’s chemical diversity and thus also for future studies.